Implementasi Pembelajaran Aqidah Akhlak dalam Menumbuhkan Karakter Disiplin dan Meningkatkan Prestasi Belajar Siswa Kelas XA di MA Hidayatul Mubtadiin Jati Agung Lampung Selatan Tahun Ajaran 2024/2025: Penelitian - Lutfiani Diah Lestari; Endang Ekowati; Anita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the implementation of Aqidah Akhlak learning in fostering the character of discipline and improving the academic achievement of Grade X A students at MA Hidayatul Mubtadiin Jati Agung, South Lampung, in the 2024/2025 academic year. This research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The findings show that the Aqidah Akhlak learning is conducted using lecture, discussion, and exemplary methods, with teacher exemplarity being the most effective in instilling moral values, particularly discipline. The discipline values instilled include punctuality, obedience to rules, and responsibility in learning. The implementation of this learning also has a positive impact on improving students' academic achievement, as evidenced by increased academic scores and learning motivation. Supporting factors for the success of implementation include the religious school environment, teacher role models, family support, and student motivation. In contrast, the inhibiting factors include limited learning media, low student interest, tardiness, and negative peer influence. Overall, Aqidah Akhlak learning plays a strategic role in shaping character and enhancing students’ academic quality holistically.